Correlates of obtaining informed consent to data linkage: Respondent, interview and interviewer characteristics - Emanuela Sala; Jonathan Burton; Gundi Knies (University of Essex, Institute for Social and Economic Research (ISER), 2010)
In the UK, in order to link individual-level administrative records to survey responses, a respondent needs to give their written consent. This paper explores whether characteristics of the respondent, the interviewer or survey design features influence consent. We use the BHPS combined with a survey of interviewers to model the probability that respondents consent to adding health and social security records to their survey responses. We find that some respondent characteristics and characteristics of the interview process within the household matter. By contrast, interviewer characteristics, including personality and attitudes to persuading respondents, are not associated with consent.
Keywords: C81; C83; 330; Consent; Data linkage; BHPS; Administrative records; Interviewer characteristics; Survey design features; Befragung; Meinungsforschung; Datenerhebung; Datenqualität; Großbritannien